Design of a new high lateral resistance sleeper and performance comparison with conventional sleepers in a curved railway track by means of finite element models - Laura Montalbán Domingo; Julia I. Real Herraiz; Clara Zamorano; Teresa Real Herraiz (Latin American Journal of Solids and Structures)
The lack of lateral resistance in a curved railway track can produce misalignment problems due to the centrifugal forces when the trains pass through. Moreover, most of the times continuous welded rails (CWR) are used in nowadays railway tracks, which can induce the track buckling as a result of thermal loads caused by high temperature gradients. A new sleeper has been designed to provide higher lateral resistance of the track. A finite element model has been developed to analyze the lateral movements of an actual curved track subjected to lateral resistance problems. Then, variations on the finite element model have been made to study the response of the track when different sleepers are used. Thus, the performance of the different sleepers in the modeled track has been analyzed, resulting that the inclusion of the new sleeper in the track can improve the lateral resistance between 39 and 55 % with respect to a track with conventional sleepers made of wood or concrete.